Ergonomics and Analytical Hierarchy Process Intervention in Transport : Motorcycle Sidecar Design to Increase Safety - Nurmianto, Eko; Sulasmono, Kresno; Nurmianto, Fikri Nurfauzan; Trikurniawan, Gilang Samudra (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2023)
This study explores the implementation of ergonomics principles and the Analytical Hierarchy Process (AHP) as interventions to enhance the safety of motorcycle sidecar designs. Recognizing the critical role of ergonomics in optimizing human-machine interactions, the research investigates how ergonomic considerations can be integrated into the design process to mitigate safety risks associated with motorcycle sidecars. Additionally, the AHP methodology is employed to systematically prioritize and evaluate various design elements, incorporating expert opinions and stakeholder preferences. The research methodology involves a comprehensive analysis of existing sidecar designs, ergonomic assessments, and the development of a structured AHP framework. Through the integration of these two approaches, the study aims to identify and prioritize key safety parameters, such as stability, visibility, and rider comfort. Practical implications of the interventions are explored, considering both rider and passenger perspectives, with a focus on minimizing the potential for accidents and injuries. The findings of this research contribute valuable insights into the application of ergonomics and AHP in motorcycle sidecar design, offering a systematic and holistic approach to enhance safety. The outcomes have the potential to inform future design practices, industry standards, and regulatory guidelines, ultimately fostering the development of safer and more user-friendly motorcycle sidecars.